Caffeine regulates osteogenic differentiation and mineralization of primary adipose-derived stem cells and a bone marrow stromal cell line. (June 2013) - Su, Shu-Jem; Chang, Kee-Lung; Su, Shu-Hui; Yeh, Yao-Tsung; Shyu, Huey-Wen; Chen, Kuan-Ming
<x xml:space="preserve">Abstract</x> Caffeine consumption reportedly influences bone mineral density and body weight. However, the effects of caffeine on bone metabolism are still controversial, and whether the dosage of caffeine influences osteogenic differentiation is yet to be clarified. In the present study, we cultured primary adipose-derived stem cells (ADSCs) and a bone marrow stromal cell line (M2-10B4) in osteogenic differentiation media containing varying concentrations of caffeine. Caffeine had biphasic effects: 0.1 mM caffeine significantly enhanced mineralization and alkaline phosphatase (ALP) activity. Consistent with these observations, a caffeine concentration of 0.1 mM upregulated the osteogenic differentiation marker genes ALP and osteocalcin (OCN), and elevated osteoprotegerin (OPG), Runt-related transcription factor 2 (RUNX2) and Sirtuin 1 (SIRT1) levels. However, a concentration of caffeine greater than 0.3 mM suppressed the differentiation of both the cell types. These findings indicate that caffeine has a beneficial effect on ADSCs and bone marrow stromal cells, enhancing differentiation to osteoblasts; this effect, which is mediated via RUNX2 activation at low doses is significantly suppressed at high doses.